Energy and Seismic Renovation Strategies for Sustainable Cities - Margani, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The principle of sustainability should be strictly connected with safety, since both aim to conserve resources: in the case of sustainability, the resources are typically thought of as environmental, while in the case of safety, the resources are basically human. In spite of this common ground, discussions on sustainability usually give insufficient attention to safety. In the last years the EU has made large investments to increase the energy efficiency of the existing building stock, paving the way for a low-carbon future; however, less effort has been made to enhance its seismic resilience. Therefore, the safety and, consequently, the sustainability of towns situated in earthquake-prone countries remain inadequate. In such countries, energy renovation actions should be combined with seismic retrofitting. However, a number of barriers considerably limit the real possibility of extensively undertaking combined retrofit actions, especially for multi-owner housing and high-rise buildings. These barriers are of different kinds: technical (e.g., unfeasibility and/or ineffectiveness of conventional retrofit solutions), financial (e.g., high renovation costs, insufficient incentives/subsidies), organizational (e.g., occupants' disruption and relocation, renovation consensus by condominium ownerships), and cultural/social (insufficient information and skills, lack of adequate policy measures for promoting renovation actions). This book aims to overcome these barriers and to bridge the gap between sustainability and safety, so to conserve both human and environmental resources.